A review of induction with rabbit a globulin in pediatric heart transplant recipients - Schweiger, Martin; Ruhparwar, Arjang (Annals of transplantation, 2018)
[b]ABSTRACT[/b] - Pediatric heart transplantation (pHTx) represents only a small proportion of cardiac transplants. Due to these low numbers, clinical data relating to induction therapy in this special population are far less extensive than for adults. Induction is used more widely in pHTx than in adults, mainly because of early steroid withdrawal or complete steroid avoidance. Antithymocyte globulin (ATG) is the most frequent choice for induction in pHTx, and rabbit antithymocyte globulin (rATG, Thymoglobulin®) (Sanofi Genzyme) is the most widely-used ATG preparation. In the absence of large, prospective, blinded trials, we aimed to review the current literature and databases for evidence regarding the use, complications, and dosages of rATG. Analyses from registry databases suggest that, overall, ATG preparations are associated with improved graft survival compared to interleukin-2 receptor antagonists. Advantages for the use of rATG have been shown in low-risk patients given tacrolimus and mycophenolate mofetil in a steroid-free regimen, in sensitized patients with pre-formed alloantibodies and/or a positive donor-specific crossmatch, and in ABO-incompatible pHTx. Registry and clinical data have indicated no increased risk of infection or post-transplant lymphoproliferative disorder in children given rATG after pHTx. A total rATG dose in the range 3.5-7.5 mg/kg is advisable.
Gesehen am 04.09.2019